Efficient removal of rhodamine B and methylene blue from water using polyurethane based porous material. Issue 12 (11th October 2022) - Kumar, Rajan; Kumar, Pawan; Panigrahi, Swati; Lakshminarasimhan, Narayanan; Shunmugam, Raja
Abstract: Here the thermally catalyzed azide‐alkyne click reaction was invoked for synthesis of functional triazole. The formed triazole was invoked to engineer polyurethane as water immiscible material. The synthesized functional triazole and polyurethane were well characterized using spectroscopic techniques—nuclear magnetic resonance (NMR), electrospray ionization mass spectrum (ESI MS), and attenuated total reflectance Fourier transform infrared (ATR‐FTIR) accordingly. The N2 adsorption–desorption isotherms confirmed the material to be mesoporous in nature with a surface area of 12.89 m 2 /g, pore volume of 0.085 cc/g, and pore radius of 7.14 nm. The characterized triazole material can be crucial with properties related to antifungal responses and UV absorption. The polyurethane material showed adsorption of amphiphilic dye—rhodamine (RH B) and methylene blue (MB). It was selective to release of rhodamine B (RH B) quite efficiently. The recycling of polyurethane reported up to cycle four revealed efficient adsorption‐release. Abstract : The metal free thermally clicked azide‐alkyne reaction was invoked for synthesis of triazole based polyurethane material, which is confirmed to be mesoporous. The polyurethane with contact angle <90° revealed its efficiency to adsorption of amphiphilic dyes—rhodamine B (RH B) and methylene blue (MB) as well as it's selectively to release of RH B.